Judeoconversos entre Lima y Cartagena: Redes económicas y sociales - Navarrete, María Cristina (2024)
The Portuguese Jewish converts who settled in the viceroyalty of Peru were dedicated to the trade of slaves, merchandise and handicraft activities. The Inquisition, under the pretext of preserving Christianity, pursued causes of faith against them.This was linked to the need for funds for the operation of the Lima Inquisition, the crisis between Spain and Portugal and the fear of allying with the Dutch enemy. The research problem is related to the persecution of the Inquisition against the new Christians accusing them of Judaizing and the punishment they received. Forty were condemned to the galleys in Spain; when they arrived in Cartagena, they evaded the authorities. The article relies conceptually and methodologically on microhistory and highlights the historiographic narrativeto transmit knowledge.